PENGARUH MODEL BRALANCING BERBANTUAN PERMAINAN MEGALA-GALA TERHADAP LITERASI BUDAYA PENDIDIKAN PANCASILA SISWA KELAS IV SDN GUGUS II BULELENG - Ketut Gde Mulyana Sahadewa; Ni Putu Candra Prastya Dewi; Ni Nyoman Lisna Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students' cultural literacy in the Pancasila Education subject, which was caused by teacher-centered learning practices and the limited use of innovative learning models based on local culture. This study aimed to analyze the effect of the Bralancing (Brain Balance Learning) model assisted by the traditional Megala-gala game on the cultural literacy of fourth-grade students in Pancasila Education at SDN Gugus II Buleleng.This study employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The population consisted of all fourth-grade students at SDN Gugus II Buleleng. The sample comprised 42 students, including 21 students in the experimental group and 21 students in the control group.The results showed that the mean posttest score of the experimental group was 113.33 (very high category), while the control group achieved a mean score of 93.90 (high category). The N-Gain analysis indicated that the experimental group achieved an average improvement of 76%, which was categorized as effective, whereas the control group showed an average improvement of 20%, which was categorized as ineffective. The hypothesis testing results revealed that the calculated t-value (t = 5.214) was greater than the critical t-value (t = 2.021), with a significance value of 0.046 (< 0.05). Therefore, H₀ was rejected and H₁ was accepted. It can be concluded that the Bralancing (Brain Balance Learning) model assisted by the traditional Megala-gala game had a significant effect on the cultural literacy of fourth-grade students in Pancasila Education at SDN Gugus II Buleleng. This learning model effectively promotes active, contextual, and enjoyable learning while strengthening students' cultural literacy and fostering the values of Pancasila.